The good, the bad, and the modified: CYLD’s post-translational tale - Macé, Yanis M.; Bidère, Nicolas; Douanne, Tiphaine (Frontiers in Cell Death, 2025)
The deubiquitinating enzyme CYLD hydrolyzes Lys63-and Met1-linked ubiquitin chains, playing a crucial role in regulating various cellular processes such as immune cell development, innate and adaptive immunity, spermatogenesis, ciliogenesis, and cell survival. CYLD also functions as a tumor suppressor and is mutated in familial cylindromatosis. This pleiotropic function implies tight regulatory mechanisms. In this review, we summarize the current knowledge on CYLD’s molecular characteristics, subcellular location, and binding partners, with a focus on its involvement in life-and-death decisions. In addition, we discuss how post-translational modifications, including phosphorylation, ubiquitination, and proteolysis, shape CYLD’s function, unveiling the potential for therapeutic intervention. Finally, we highlight the remaining challenges that need to be overcome to deepen our understanding of this crucial enzyme.